Moisture diffusivity determination of different parts of longan fruit - S. Janjai (2018)
The components of the longan fruit were modeled as sphere for seed, cylinder for seed stalk, and slab for seed coat, shell, and flesh. The moisture diffusivities were determined by minimizing the sum of square of derivations between the predicted and experimental values of moisture content of thin layer drying under controlled conditions of air temperature and relative humidity. Experimental data were obtained from thin layer drying of the components in the form of sphere for seed, cylinder for seed stalk and slab for seed coat, shell and flesh. Air temperatures of 50, 60, 70, and 80C and relative humidity in the range of 1.5-13.33% were used. The mean diffusivity of flesh of longan fruit increased with temperature, but the diffusivities of shell, seed coat, seed, and seed stalk were independent of temperature. The moisture diffusivities of shell and seed coat were much lower than those of the other parts of the longan.